DETERMINATION OF THE EFFECTS OF RADIO SIGNAL STRENGTH AND ATTENUATION AS A FUNCTION OF LINEAR DISTANCE AND SOME ATMOSPHERIC CONDITIONS ON TSBS, JALINGO, TARABA STATE - Yabwa, Dlama; Kanu, O. M.; Dawaki, M. I. (FUDMA JOURNAL OF SCIENCES, 2023)
Taraba state broadcasting station (TSBS) is situated in Jalingo with coordinates (8º 56N 11º 55E) with transmission frequency of 90.6 MHz covering a distance of 250 km and operates for up to fifteen hours a day. The signal strength of TSBS Jalingo was taken as a function of distance and some variables which are temperature, refractivity, humidity, solar radiance and other ionospheric factors in cognizance. The measured values shows negative correlation between the signal strength of TSBS with the linear distance as measured both in volt per meter and in decibels these values were calculated based on a reference distance of 1 km with value of 0.7746 (v/m) or -2.62 (dB).The signal strength values with the daily hourly record did not match, which is in excellent agreement from literature. While atmospheric factor (refractivity) as thus observed is seen that high refractivity leads to less radio wave propagation and vice versa. This research work can be employed in communications technology, to determine the effects of “topographical terrain on frequency propagation” when citing any other Radio Station in Nigeria.